Understanding of Eosinophilic Esophagitis in Children - A Comprehensive Study on Epidemiology, Clinical Manifestations, Diagnosis and Innovative Treatment Modalities - Zarzycka, Marta; Sikora, Marcelina; Plewniok, Ines; Maj-Dziedzic, Monika; Dubiel, Jeremiasz; Brzozowska, Anna; Maj, Adrian; Śmietana, Greta; Warno, Martyna; Kozik, Wiktor (Journal of Education, Health and Sport, 2024)
Introduction: In the late 1960s, probable cases of eosinophilic esophagitis (EoE) emerged, initially linked to esophageal rings and congenital causes or gastroesophageal reflux disease (GERD). Doubts about the GERD association arose due to poor responses to antisecretory therapy. EoE is now a significant pediatric health concern, impacting 1 to 7 cases per 10,000 children. Purpose of the Study: This study aims to comprehensively explore EoE's epidemiology, etiology, subtypes, clinical manifestations, diagnostic methods, and treatment modalities. Materials and Methods: The study employs a cross-sectional analysis of pediatric EoE patients, utilizing endoscopic evaluation and histological assessment. Three distinct EoE subtypes are identified based on pathogenic characteristics. Clinical manifestations, diagnostic methods, and treatments, including endoscopy, are examined. Results: Clinical manifestations span a broad spectrum in the pediatric population. Diagnostic methods include endoscopy, esophageal manometry, impedance-pH monitoring, capsule endoscopy, and string tests. Three distinct EoE subtypes are identified with unique characteristics. Treatment modalities involve dietary management, proton pump inhibitors, topical corticosteroids, biologic therapies, allergen immunotherapy, and endoscopic interventions. Conclusion: Formerly associated with GERD, EoE is now a significant pediatric health concern. The study underscores the importance of comprehensive diagnostic approaches and diverse treatment modalities, including promising biologic therapies and allergen immunotherapy. Understanding these aspects is crucial for effective management and improved outcomes in patients.